2018
DOI: 10.1016/j.ica.2018.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Rhodium(II) amido/Rhodium(I) aminyl complexes

Abstract: Reaction of the Rh(II) dimer [LRh] 2 (μ-Br) 2 (L = ([2,6-Me 2 C 6 H 3 NCMe] 2 CH) with the bulky amide LiNH (2,6-i Pr 2 C 6 H 3) leads to a monomeric Rh(II) amide with a T-shape N 3 Rh arrangement and a pronounced agostic interaction. Reaction with the less bulky LiNH(2,6-Me 2 C 6 H 3) results in benzylic C-H activation to a binuclear complex with a unique aza-xylylene bridging mode. With LiNHC 6 H 5 we observe initial formation of [LRh] 2 (μ-NHPh) 2 followed by N,C2′ coupling of two anilines. These reactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…They allow for the investigation of intentional carbon doping without interference from unintentionally incorporated carbon. Doping of GaN with propane in HVPE revealed that carbon together with oxygen and hydrogen results in at least two transitions of yellow defect luminescence (YL) with a deep acceptor involved . An investigation in rf plasma‐assisted MBE with CBr 4 as carbon source revealed that carbon in concentrations up to 10 19 cm −3 has no negative influence on structural properties of GaN but compensates Si donors .…”
Section: Introductionmentioning
confidence: 99%
“…They allow for the investigation of intentional carbon doping without interference from unintentionally incorporated carbon. Doping of GaN with propane in HVPE revealed that carbon together with oxygen and hydrogen results in at least two transitions of yellow defect luminescence (YL) with a deep acceptor involved . An investigation in rf plasma‐assisted MBE with CBr 4 as carbon source revealed that carbon in concentrations up to 10 19 cm −3 has no negative influence on structural properties of GaN but compensates Si donors .…”
Section: Introductionmentioning
confidence: 99%
“…Using the V III precursor, [(PNP)VCl 2 ], 16 we sought to install a sterically encumbering robust ancillary ligand to offer more kinetic stabilization and discourage decomposition pathways. Accordingly, transmetalation of [(PNP)VCl 2 ] with Li(THF)(NHAr) 17 in toluene cleanly produced red crystals of [(PNP)V(NHAr)Cl] (1) in 79% crystalline yield (Scheme 1).…”
mentioning
confidence: 99%
“…Using the V III precursor, [(PNP)­VCl 2 ], we sought to install a sterically encumbering robust ancillary ligand to offer more kinetic stabilization and discourage decomposition pathways. Accordingly, transmetalation of [(PNP)­VCl 2 ] with Li­(THF)­(NHAr) in toluene cleanly produced red crystals of [(PNP)­V­(NHAr)­Cl] ( 1 ) in 79% crystalline yield (Scheme ). To install a methylidene, we then treated 1 with a Grignard MgCl­(CH 3 ) in toluene at room temperature to cleanly afford [(PNP)­V­(NHAr)­(CH 3 )] ( 2 ) in 80% yield (Scheme ).…”
mentioning
confidence: 99%